My i Wy? Spór o kształt poezji pomiędzy pokoleniem ’68 a pokoleniami wcześniejszymi - Misiak, Iwona (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2024)
The polemic between the generation of ’68 and earlier generations, such as those of ‘Współczesność’ and ‘Hybrydy’, concerned the nature of poetry and its relation to reality. This collection of texts from the period 1967–1975 presents various driving forces for polemics as well as the intensity of intergenerational discussions, cultural climate of the era and oppressiveness of cultural policy in the People’s Republic of Poland. The participants in those events not only entered into vigorous discussion, they also often collaborated; influencing the intriguing, diverse shape of poetry and meta-poetic reflection. The anthology includes texts by established New Wave writers and representatives of older generations, as well as still lesser-known New Wave authors. Two events stand out in the course of these discussions: The 9th Kłodzko Poetic Spring and the subsequent poetic dialogue between Zbigniew Herbert and Ryszard Krynicki. These stories illustrate the dynamics of polemics in which the manifestation and confrontation of differing ideas leads to a mutual and creative understanding.
Us and Them? The Polemic Over the Nature of Poetry Between the Generation of ’68 and Earlier Generations